2018
DOI: 10.1002/chem.201706033
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complex‐Controlled Regio‐, Diastero‐ and Enantioselective 1,3‐Dipolar Cycloaddition of Azomethine Ylides with Benzo[b]thiophene Sulfones

Abstract: The Cu(MeCN) PF /DTBM-Segphos complex catalyzed the highly diastereo- and enantioselective 1,3-dipolar cycloaddition of azomethine ylides with benzo[b]thiophene sulfones with the usual regiochemistry to give single isomers of the exo-cycloadducts in good yields. In contrast, the AgOAc/ThioClickFerrophos complex catalyzed the reaction with atypical regiochemistry to give the endo-cycloadducts as major products with excellent enantioselectivities. Thus, the choice of chiral metal complex enabled the regio- and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In 2017 Fukuzawa et al reported a highly regio-and diastereoselective 1,3-dipolar cycloaddition for obtaining chiral sulfolanes by using Cu(MeCN) 4 PF 6 /DTBM-Segphos 199 or AgOAc/ThioClickFerrophos 200 complex catalyzed (Scheme 52). [71] In these catalytic systems, the reaction catalyzed by Cu(MeCN) 4 PF 6 /DTBM-Segphos 199 complex led to the formation of exo-cycloadducts 201 with high enantioselectivity. Interestingly, when using AgOAc/ThioClickFerrophos 200 complex as catalyst, an unusual regiochemistry could be found and the endo-cycloadducts 202 with high enantioselectivity was provided as the main product.…”
Section: Azomethine Ylidesmentioning
confidence: 99%
“…In 2017 Fukuzawa et al reported a highly regio-and diastereoselective 1,3-dipolar cycloaddition for obtaining chiral sulfolanes by using Cu(MeCN) 4 PF 6 /DTBM-Segphos 199 or AgOAc/ThioClickFerrophos 200 complex catalyzed (Scheme 52). [71] In these catalytic systems, the reaction catalyzed by Cu(MeCN) 4 PF 6 /DTBM-Segphos 199 complex led to the formation of exo-cycloadducts 201 with high enantioselectivity. Interestingly, when using AgOAc/ThioClickFerrophos 200 complex as catalyst, an unusual regiochemistry could be found and the endo-cycloadducts 202 with high enantioselectivity was provided as the main product.…”
Section: Azomethine Ylidesmentioning
confidence: 99%
“…[22] The reaction between azomethine ylides and sulfinyl or sulfonyl groups has been reported in the past, with diverse results. [23][24][25][26][27][28][29][30] Among those references, it is interesting to mention two publications in which different strategies were developed starting from 1,2 diactivated sulfonyl acrylates to obtain exo adducts with a regiochemistry controlled by the sulfonyl group [30] or endo adducts with the opposite regiochemistry, so controlled by the ester moiety. [26] The origin of these switch on diastereo-and regioselectivity relies on the use of a copper or silver catalyst, respectively, and different ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of methods for the asymmetric synthesis of polyfunctional sulfones is valuable. The most notable of them are Ag- and Cu-catalyzed 1,3-dipolar cycloaddition reactions, which allows to obtain chiral cyclic sulfones with high enantioselectivity [1012]. Also non-racemic cyclic sulfones can be obtained by the Diels–Alder reaction, catalyzed by chiral Lewis acids or organocatalysts.…”
Section: Introductionmentioning
confidence: 99%